Augmented Renal Clearance in Pediatric Patients With Febrile Neutropenia Associated With Vancomycin Clearance. Issue 3 (June 2016) - Hirai, Keita; Ihara, Setsuko; Kinae, Ayumi; Ikegaya, Kenichi; Suzuki, Masayuki; Hirano, Keiko; Itoh, Kunihiko
Abstract : Background: Vancomycin (VCM) dosage optimization in the early stages of therapy is required to achieve target trough serum concentrations, particularly in critically ill patients. Augmented renal clearance (ARC), commonly characterized by an enhanced renal clearance, has been associated with subtherapeutic concentrations of antibiotics. The aim of this study was to investigate the risk factors including febrile neutropenia for both ARC and VCM clearance in Japanese pediatric patients. Methods: A total of 109 pediatric patients with normal renal function were included in this observational study. From VCM serum concentrations, individual VCM clearance was estimated by the Bayesian method using a 1-compartment model. Patients were classified on the basis of the presence of febrile neutropenia, cancer, trauma, systemic inflammatory response syndrome, and surgical operation. Risk factors for ARC, as defined by estimated glomerular filtration rate (eGFR) above median value (≥160 mL·min −1 ·1.73 m −2 ), were evaluated. Results: Febrile neutropenia was only an independent risk factor for ARC (odds ratio, 5.86; 95% confidence interval, 1.98–21.66, P = 0.0030), which was the result of a stepwise multivariate logistic regression analysis. Although univariate analysis demonstrated a significant association of febrile neutropenia with VCM clearance, the significant independent factors of VCM clearance were age and eGFR but not febrile neutropenia, as estimated by the stepwise multivariate linear regression analysis. Conclusions: This observational study concluded that febrile neutropenia, a significant risk factor for ARC, indirectly influenced VCM clearance towing to an elevated eGFR. Cancer, trauma, systemic inflammatory response syndrome, and surgical operation were not significantly associated with ARC; however, more studies are needed to validate this observation. Adjustment of the initial dosage of VCM is required for achieving optimal therapeutic concentrations in pediatric patients with febrile neutropenia.